Optimalisasi Google Service dalam Digitalisasi Aktivitas Organisasi: Implementasi pada KIPAN - Muhammad Tulus Akbar; Maryama Kurnia Amri; Yusrizal; Adri Flouren Timor; Rolly Gios Sholid; Hawari Alhaq (PT. Meja Ilmiah Publikasi, 2026)
Digital transformation in organizations supports the acceleration of organizational change in managing their activities. One of the platforms that facilitates this process is Google Services, which enables integrated collaboration, communication, and data management. This community service program aims to optimize the use of Google Services to support the digitalization of organizational activities at KIPAN (Kader Inti Pemuda Anti Narkoba) of Jambi Province. The method employed was a participatory-perceptual approach through training, socialization, and hands-on practice involving 11 core administrators of KIPAN. Data were collected through field observations and analyzed using descriptive qualitative techniques. The results showed that 91% of participants had a very good understanding of the material presented, 73% were able to align the material with practical application, and 36% were capable of developing tasks and innovations using Google Services. These findings indicate that the program was effective in improving participants’ digital capacity, although further mentoring is still needed to strengthen innovation aspects. Overall, this program contributes to strengthening organizational capacity through the systematic use of digital technology.